Processing inflectional morphology: ERP evidence for decomposition of complex words according to the affix structure. (July 2019) - Regel, Stefanie; Opitz, Andreas; Müller, Gereon; Friederici, Angela D.
Abstract: This study investigated the processing of inflectional morphology by registrating event-related brain potentials (ERPs) during sentence reading. In particular, we examined nouns combined with affixes that have distinct structural characteristics as proposed by morphological theory. Affixes were either complex consisting of functionally distinguishable subparts as occurring for German plural morphology, or simple consisting of one part only. To test possible differences in processing these affixes we compared grammatical nouns [e.g., Kartons (cartons)] to ungrammatical ones (e.g., * Kartonen ) in two different syntactic contexts represented by a complex, or simple affix. The ERPs showed that ungrammatical nouns consisting of complex affixes elicited a left anterior negativity (LAN) reflecting enhanced morphosyntactic processing, which was absent for equivalent nouns consisting of simple affixes. This finding suggests that inflected words are decomposed dependent on the affix structure, whereby the affixes themselves seem to consist of morphological subparts in accordance with current morphological theories (Müller, 2007; Noyer, 1992 ). Moreover, ungrammatical nouns elicited early (reduced P200) and late (P600) ERP components relative to their grammatical equivalents, which implies an engagement of syntactic processes presumably based on intially enhanced pre-lexical processing of these irregularized nouns. The findings are discussed with respect to theoretical and neuropsychological accounts to inflectional morphology.